High Resolution Glassless 3D with Head‐Tracking System. Issue 1 (June 2014) - Koito, Takeo; Higashi, Amane; Kasai, Taiki; Suzuki, Daichi; Yang, Yingbao; Takizawa, Keiji
Abstract We have developed a new high resolution glasses‐less 3D LCD with head‐tracking technology. The 3D crosstalk has been suppressed to less than 2% at any position of the viewer by applying a fine pitch barrier and proper aperture design to the display.